Edukasi Mc.Kenzie Cervical Exercise terhadap Nyeri Leher pada Pembatik di Seberang Kota Jambi - Indah Permata Sari; Faridah Faridah (3031-8572, 2022)
Neck pain is pain that arises in the area bounded above by the nuchal line and below by a transverse imaginary line through the end of the first thoracic spinous process and laterally by the lateral margin of the neck. Prevalence of neck pain cases 426,000, 25-31 years of age 5%, 32-38 years 13%, 39-45 years 25%, 46-52 years 20%, 53-59 years 20%, 60-66 as much as 6%. The community service activity was carried out on February 12, 2022 with 30 batik makers participating with pre and post assessment instruments using a numerical rating scale. Education by giving leaflets about neck pain and mc.kenzie cervical exercise, namely stretching and active exercise, is done 1 repetition with 8 repetitions of the movement, then demonstration of the movement to batik workers across Jambi City. The results of this community service obtained an increase in knowledge with a good percentage of understanding of respondents 26 people (86%), while 4 people (14%) and ability of respondents to practice Mc. Kenzie cervical exercise after exercise also experienced an increase